1996
DOI: 10.1007/bf00265213
|View full text |Cite
|
Sign up to set email alerts
|

Deglutition after supracricoid laryngectomy: Compensatory mechanisms and sequelae

Abstract: This study is based on the videofluorographic exploration of deglutition in 14 patients who were treated by supracricoid laryngectomy. The choice of this population rests on two criteria: a 1-year postoperative delay, and absence of residual deglutition disorders elicited by patient history. Asymptomatic aspiration was seen in 6 cases. In the cricohyoidoepiglottopexies (CHEP), aspiration occurred uniquely in patients who did not recuperate satisfactorily from epiglottic dynamics. The deglutition sequelae are l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
43
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 8 publications
3
43
0
Order By: Relevance
“…Furthermore, food might collect around the arytenoids thus, increasing the risk of aspiration. 12,13 To minimise PP, elderly patients and those with poor pulmonary function tests are considered not eligible for conservative laryngeal surgery because of the high risk of aspiration, due to a decreased ability to cough and clear secretions. Despite this selection, PP still represents the most frequent potentially life-threatening complication in partial laryngectomized patients, requiring more intensive care, delay rehabilitation and discharge from the hospital and inevitably leading to greater health care costs.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, food might collect around the arytenoids thus, increasing the risk of aspiration. 12,13 To minimise PP, elderly patients and those with poor pulmonary function tests are considered not eligible for conservative laryngeal surgery because of the high risk of aspiration, due to a decreased ability to cough and clear secretions. Despite this selection, PP still represents the most frequent potentially life-threatening complication in partial laryngectomized patients, requiring more intensive care, delay rehabilitation and discharge from the hospital and inevitably leading to greater health care costs.…”
Section: Discussionmentioning
confidence: 99%
“…8 Differences with deglutition have also been recognized with supracricoid laryngectomy when comparing cricohyoidepiglottopexy and cricohyoidopexy. 9 Others have studied postoperative outcomes. Rademaker et al 10 found that patients with supraglottic laryngectomy returned to oral intake in a median time of 26 days, and patients with extended supraglottic laryngectomy returned to preoperative diets in a median time of 91 to 335 days.…”
Section: Accepted 31 May 2001mentioning
confidence: 99%
“…There are references to the continuation of severe dysphagia in cases of CHEP where there was no functional dynamic compensation of the epiglottis. 16 There was no statistically significant difference or noteworthy percentage difference between the presence of one or two arytenoids and functional progression of voice and swallowing. Since only one arytenoid was preserved in most cases, similar to other published trials, 17 further studies with larger series, in which two arytenoids are preserved, would be enlightening.…”
Section: Discussionmentioning
confidence: 77%